Interdiffusion and formation of intermetallic compounds in high-temperature power electronics substrate joints fabricated by transient liquid phase bonding. (October 2022) - Imediegwu, Chidinma; Graham, Samuel; Pahinkar, Darshan G.; Narumanchi, Sreekant; Paret, Paul; Major, Joshua
Abstract: Power electronics packages typically comprise a dielectric substrate bonded to a metal layer and attached to heat sinks using a low-thermal-conductivity solder. These multiple layers increase the effective thermal resistance of the package and are responsible for package failures under cyclic thermal loads. Bonding the aluminum nitride dielectric layer (AlN) directly to a low coefficient of thermal expansion (CTE) aluminum silicon carbide (AlSiC) cold plate using copper‑aluminum (Cu-Al) transient liquid phase (TLP) bonding has been shown to improve the mechanical reliability of the power electronic packages while making the package more compact by bringing the cooling solutions closer to the devices. This study aims to characterize the Cu-Al bonds formed during the TLP bonding of AlSiC with three different power electronics substrates: pure aluminum nitride (AlN), aluminum (DBA), and copper (DBC). The material compositions and microstructures of the bonds were analyzed using scanning electron microscopy (SEM), x-ray spectroscopy (EDS), confocal scanning acoustic microscopy (C-SAM), and x-ray diffraction (XRD). α-Al solid compound was identified as the dominant phase in AlN-AlSiC and Al-AlSiC, with a notable presence of SiC particles. In contrast, three intermetallic phases – θ-CuAl2, η-CuAl, and γ′- Cu9 Al4 – were observed in the Cu-AlSiC bond. A computational solid-state diffusion model was developed to predict the intermetallic compounds (IMCs) formed during Cu-Al TLP bonding in each system, which supported the observation that an initial Cu volume fraction of 20 % in the material layers produced a final bond composition of >95 % Al with minimal IMC growth. However, increased Cu concentrations produced higher concentration gradients, leading to increased growth of IMCs, Kirkendall voids, and interstitial cracks. Highlights: Transient liquid phase bonding of AlN to AlSiC compacts power modules stack Lower CTE mismatch enhances thermomechanical reliability. Bonding technique is useful to attach commercial substrates to heat sinks. Formation of intermetallic compounds increases crack development in the bond layer. Diffusion model can aid in determination of intermetallic compounds formed.